Propagation of Forestiera phillyreoides: A potential species for restoration in north-central Mexico - Martínez-Calderón, Víctor Manuel; Sosa-Ramírez, Joaquín; Torres-González, Jorge Alejandro; Mendieta-Vázquez, Araceli Guadalupe; Sandoval-Ortega, Manuel Higinio (Instituto de Ecología, A.C., 2020)
Forestiera phillyreoides is a species of wide distribution in semi-arid and subtropical areas of the country. Despite being a common species, there is no information about its propagation. Therefore, the objective was to generate information about its fruiting, its germination under different pre-germinative treatments and the growth of seedlings in the nursery. A review of herbarium and field trips was carried out to know the fruiting. Eight pre-germinative treatments were evaluated: control, 24 h water immersion, sulfuric acid immersion (3 min, 6 min, 9 min and 12 min), manual endocarp removal plus 24 h immersion and 24 h immersion in 500 ppm of GA3. Seedlings were cultivated for seven months, at the end of the period, the height, diameter, the aerial dry weight/root dry weight ratio (PSA/PSR), robustness index and Dickson quality index were calculated. Fruiting occurs during the months of March to June. The endocarp removal treatment had the highest germination percentage (95 ± 4.08), a positive response to sulfuric acid treatments was presented, the GA3 treatment had negative effects on germination. The seedlings reached a height of 31.65 cm ± 5.01 cm and a diameter of 5.13 mm ± 0.34 mm, the PSA / PSR values (1.02 ± 0.17) indicate drought resistance. The treatments that remove or degrade the endocarp are the most appropriate to achieve better germination. At seven months it reached the necessary parameters for use in reforestation. The information generated provides the basis for the propagation of F. phillyreoides.